Geologic and Structural Evolution of the NE Lau Basin, Tonga: Morphotectonic Analysis and Classification of Structures Using Shallow Seismicity - Anderson, Melissa O.; Norris-Julseth, Chantal; Rubin, Kenneth H.; Haase, Karsten; Hannington, Mark D.; Baxter, Alan T.; Stewart, Margaret S. (Frontiers in Earth Science, 2021)
The transition from subduction to transform motion along horizontal terminations of trenches is associated with tearing of the subducting slab and strike-slip tectonics in the overriding plate. One prominent example is the northern Tonga subduction zone, where abundant strike-slip faulting in the NE Lau back-arc basin is associated with transform motion along the northern plate boundary and asymmetric slab rollback. Here, we address the fundamental question: how does this subduction-transform motion influence the structural and magmatic evolution of the back-arc region? To answer this, we undertake the first comprehensive study of the geology and geodynamics of this region through analyses of morphotectonics (remote-predictive geologic mapping) and fault kinematics interpreted from ship-based multibeam bathymetry and Centroid-Moment Tensor data. Our results highlight two notable features of the NE Lau Basin: 1) the occurrence of widely distributed off-axis volcanism, in contrast to typical ridge-centered back-arc volcanism, and 2) fault kinematics dominated by shallow-crustal strike slip-faulting (rather than normal faulting) extending over ∼120 km from the transform boundary. The orientations of these strike-slip faults are consistent with reactivation of earlier-formed normal faults in a sinistral megashear zone. Notably, two distinct sets of Riedel megashears are identified, indicating a recent counter-clockwise rotation of part of the stress field in the back-arc region closest to the arc. Importantly, the Riedel structures identified in this study directly control the development of complex volcanic-compositional provinces, which are characterized by variably-oriented spreading centers, off-axis volcanic ridges, extensive lava flows, and point-source rear-arc volcanoes. This study adds to our understanding of the geologic and structural evolution of modern backarc systems, including the association between subduction-transform motions and the siting and style of seafloor volcanism.